1997
DOI: 10.2166/wst.1997.0370
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the need of thermodynamic considerations in modelling of anaerobic environmental bioprocesses

Abstract: For modeling of biological processes that operate close to the dynamic equilibrium (eg. anaerobic processes), it is critical to prevent the prediction of positive reaction rates when the reaction has already reached dynamic equilibrium. Traditional Michaelis-Menten based models were found to violate the laws of thermodynamics as they predicted positive reaction rates for reactions that were endergonic due to high endproduct concentrations. The inclusion of empirical “product inhibition factors” as suggested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…When interpreted in the context of our overall thermodynamic model it is clear that Mosche and Jordening [31] have simply demonstrated that propionate degradation was not the rate controlling step of their batch anaerobic digestions. A number of authors argue that thermodynamic considerations must be included in bio-kinetic studies of anaerobic digestion [20,30,32,33]. Kaspar and Wuhrman [30], and Hoh and Cord-Ruwisch [32,33] empirically demonstrated that propionate degradation in an operating digester proceeds close to equilibrium (DG = 0) despite the methanogenesis reaction being far from equilibrium.…”
Section: Lfas Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…When interpreted in the context of our overall thermodynamic model it is clear that Mosche and Jordening [31] have simply demonstrated that propionate degradation was not the rate controlling step of their batch anaerobic digestions. A number of authors argue that thermodynamic considerations must be included in bio-kinetic studies of anaerobic digestion [20,30,32,33]. Kaspar and Wuhrman [30], and Hoh and Cord-Ruwisch [32,33] empirically demonstrated that propionate degradation in an operating digester proceeds close to equilibrium (DG = 0) despite the methanogenesis reaction being far from equilibrium.…”
Section: Lfas Decompositionmentioning
confidence: 99%
“…A number of authors argue that thermodynamic considerations must be included in bio-kinetic studies of anaerobic digestion [20,30,32,33]. Kaspar and Wuhrman [30], and Hoh and Cord-Ruwisch [32,33] empirically demonstrated that propionate degradation in an operating digester proceeds close to equilibrium (DG = 0) despite the methanogenesis reaction being far from equilibrium. The observations of these groups show that the acclimatisation of anaerobic sludges selects the best microbial populations [47] which, under the proper oxidation/reduction conditions are able to effectively degrade the linear fatty acids produced in the acido-acetogenesis (fermentation) until the system approaches the equilibrium state.…”
Section: Lfas Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 as the difference between ΔG for acetate production and ethanol production from CO 2 and H 2 . Typically in the rumen or anaerobic digester, the ratio of H 2 to CO 2 is about 0.001 (Hoh and Cord-Ruwisch, 1997;Ungerfeld and Kohn, 2006). Under such conditions, it is thermodynamically feasible to convert these gases to methane with production of 1 ATP per mole of methane, and H 2 is readily used to make methane in the rumen, keeping the H 2 pressure low.…”
Section: Cellulosic Ethanolmentioning
confidence: 99%
“…cow's rumen) is explained as near-equilibrium in accordance with the second law of thermodynamics. First, the values of ΔG are near zero for many reactions in the rumen (Kohn and Boston, 2000;Ungerfeld and Kohn, 2006), or a manure or a sewage digester (Hoh and Cord-Ruwisch, 1997;Jackson and McInerney, 2002) including methane or acetic acid production from CO 2 and H 2 and interconversion of acids. Furthermore, the rates of interconversion of one acid to another are similar in each direction as measured using isotopic labels (Ungerfeld and Kohn, 2006).…”
Section: Introductionmentioning
confidence: 99%